Persistence and reservoirs of Saccharomyces cerevisiae biodiversity in different vineyard niches - Gonzalez, Magali Lucia Rosa (2019)
Highlights: S. cerevisiae vineyard populations dynamically changed during grape growth cycle. Strains from ripe grapes showed highest diversity and distribution across vineyard. Buds in winter and bark from sprouting to harvest behaved as S. cerevisiae reservoirs. Population biodiversity analysis revealed high differentiation among vineyard niches. Environmental temperature conditioned the S. cerevisiae population differentiation.